Legal issues in partnership law concerning musharakah al-mutanaqisah practised by Islamic financial institutions in Malaysia - Md Dahlan, Nuarrual Hilal (2014)
One of the Islamic Banking products in Malaysia is Islamic Partnership Home Financing Facility-Musharakah al-Mutanaqisah (‘MM’).It is a trite practice that for Islamic Banking products to be legal and shariah compliant, the products must fulfill the requirements of the shariah (Islamic law) and Malaysian law. Under the Malaysian law, Partnership Act 1961 (Act 135)(‘PA’) governs partnership.It follows that, as a matter of course, MM shall also be governed by the PA. This paper will highlight the issues in the provisions of the existing PA with regard to MM.The authors use a legal research methodology to under take the research.The authors also provide, at the end part of this paper, some suggestions in dealing with the issues to warrant the validity of the MM in the legal perspective.